Multiple classifier systems : 12th International Workshop, MCS 2015, Günzburg, Germany, June 29-July 1, 2015, Proceedings /: 12th International Workshop, MCS 2015, Günzburg, Germany, June 29-July 1, 2015, Proceedings. (2015) - Unknown
No abstract available